Calendar sheet. V.I. Lenin (in the middle) and T. Samueli (at the right of Lenin dressed in a leather jacket) on the Red Square during the celebration of the Vseobuch troops. Compare: 69/39 A, page 203
Calendar sheet. V.I. Lenin (in the middle) and T. Samueli (at the right of Lenin dressed in a leather jacket) on the Red Square during the celebration of the Vseobuch troops. Compare: 69/39 A, page 203.